Evaluation of effective factors in decreased bone density in patients with osteoporosis and osteopenia - Nasser Aghamohammadzadeh (MD) (مجله دانشگاه علوم پزشکی گرگان, 2009)
Background and Objective: Osteoporosis is the most common metabolic bone disease that characterized by reduced bone strength. The aim of this study was to evaluate the prevalence of effective factors in decreased bone density and secondary causes of osteoporosis.